2017
DOI: 10.1108/he-01-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

A social norms approach to changing school children’s perceptions of tobacco usage

Abstract: A s o ci al n o r m s a p p r o a c h t o c h a n gi n g s c h o ol c hil d r e n's p e r c e p tio n s of t o b a c c o u s a g e S h eik h, A, Vad e r a , S, R av ey, MI, Lov a t t, G a n d Kelly, G h t t p:// dx. doi.o r g/ 1 0. 1 1 0 8/ h e-0 1-2 0 1 7-0 0 0 6 Ti t l e A s o ci al n o r m s a p p r o a c h t o c h a n gi n g s c h o ol c hil d r e n's p e r c e p tio n s of t o b a c c o u s a g e A u t h o r s S h eik h, A, Vad e r a , S, R av ey, MI, Lov a t t, G a n d Kelly, G Typ e Articl e U RL This v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…The analysis of the articles showed that they will be more effective when combined with other media. The other media in question could be education from the health workers, videos, demonstrations, Focus Group Discussions (FGD) and games (Sheikh, Vadera, Ravey, Lovatt, & Kelly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the articles showed that they will be more effective when combined with other media. The other media in question could be education from the health workers, videos, demonstrations, Focus Group Discussions (FGD) and games (Sheikh, Vadera, Ravey, Lovatt, & Kelly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we have demonstrated the value of a SNA to changing the attitudes and norms of young people as every question that was included in both the baseline and repeat surveys showed a measurable change. More generally, there is a growing body of evidence that illuminates the centrality of social norms in the development of positive behavior (Elsey et al 2015;Sheikh et al 2017), whilst here we provide evidence of its value in relation to healthy relationship norms and behaviors. Moreover, it is widely accepted that the ways in which to successfully address DVA when it presents in relationships, in adolescence or adulthood, is through an approach which targets norms (Stanley et al 2015;Cislaghi and Heise 2017) within a school environment as 'shifting social norms in the peer group [is] a key mechanism of change' (Stanley et al 2015: v).…”
Section: Discussion and Concluding Commentsmentioning
confidence: 82%
“…As a consequence, a social norming approach (SNA) is based upon a well-articulated theory of behavior and evidence-based methodology for addressing health and social justice issues (Berkowitz 2012). In work with young people, it has increasingly been utilized in prevention work around alcohol use and smoking (Elsey et al 2015;Sheikh et al 2017). More importantly, it is during the last decade that social norms theory has gained momentum as a potentially useful means of addressing gender-based violence and domestic abuse (Cislaghi and Heise 2017).…”
Section: A Social Norms Approachmentioning
confidence: 99%
“…Social norms may be a valuable entrypoint for tobacco control efforts, based on longitudinal social network evidence suggesting that cessation behavior can spread in a network through proximal and distal ties [36][37][38]. Social norms interventions for tobacco use often involve correcting normative misperceptions (e.g., [39]) and using peer leaders to drive activities and dialogue around change (e.g., [40]). The evidence base for these approaches is mixed, and further research is needed to understanding if and how social norms add value to tobacco reduction, cessation, or prevention interventions.…”
Section: Social Norms and Tobacco Usementioning
confidence: 99%